2023
DOI: 10.1590/0103-6440202304980
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene enhances bone neoformation in calvaria bone defects of ovariectomized rats

Abstract: Osteoporosis can affect a significant part of the population and fractures are the most common complications associated with this disease, leading to high public health costs. Thus, the prevention of fractures is relevant to individuals with signs and symptoms as well as to the health system. Postmenopausal osteoporosis has been associated with oxidative stress, emphasizing the importance of an efficient defense system to maintain bone health. Lycopene is a carotenoid with antioxidant properties that may stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
2
0
0
Order By: Relevance
“…In the present study, we found that LYC treatment did ameliorate bone quality evidenced by an improvement of bone microstructure, mechanical strength and material profiles in OVX rats. This is in agreement with the previous investigations [49][50][51]. Our group also found that LYC improves bone quality in obese mouse [22].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we found that LYC treatment did ameliorate bone quality evidenced by an improvement of bone microstructure, mechanical strength and material profiles in OVX rats. This is in agreement with the previous investigations [49][50][51]. Our group also found that LYC improves bone quality in obese mouse [22].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we found that LYC treatment did ameliorate bone quality evidenced by an improvement of bone microstructure, mechanical strength, and material profiles in OVX rats. This is in agreement with the previous investigations [54][55][56]. Our group also found that LYC improves bone quality in obese mice [23].…”
Section: Discussionsupporting
confidence: 93%